PENGARUH SALINITAS TERHADAP PERTUMBUHAN DAN PERKEMBANGAN AKAR SEMAI MANGROVE Rhizophora apiculata Blume - Desya Alvionita Keliat; Mohammad Basyuni; Budi Utomo (Program studi Kehutanan USU, 2016)
Rhizophora apiculata is easy species to be found and widely distributed. The purpose this research is to know the best concentration of salinity for growing seedlings of mangrove as refrence to rehabilitate mangrove forest. Effect of salinity on the growth and root development in mangrove Rhizophora apiculata Blume seedlings at Greenhouse Faculty of Agriculture and Laboratory of Ecology, University of Sumatera Utara from May 2015 until October 2015. Five level concentration of salinity was used namely 0%, 0,5%, 1,5%, 2%, and 3% with ten of repeatation. The research measured the parameters of height seedlings, diameter, leaves thickness, wide of leaves, primary root, lateral root, long of primary root, long of lateral root, diameter of primary root, diameter of lateral root, water content of shoot, water content of root, and shoot ratio. We found that the best growing Rhizophora apiculata seedlings was at 0,5% salinity level.Keywords: Development, Mangrove, Growing, Rhizophora apiculata Blume, Salinity